IL-17-producing [gamma][delta] T cells and neutrophils conspire to promote breast cancer metastasis - Coffelt, Seth B; Kersten, Kelly; Doornebal, Chris W; Weiden, Jorieke; Vrijland, Kim; Hau, Cheei-Sing; Verstegen, Niels J. M; Ciampricotti, Metamia; Hawinkels, Lukas J. A. C; Jonkers, Jos; de Visser, Karin E (Nature (London), 2015)
Metastatic disease remains the primary cause of death for patients with breast cancer. The different steps of the metastatic cascade rely on reciprocal interactions between cancer cells and their microenvironment. Within this local microenvironment and in distant organs, immune cells and their mediators are known to facilitate metastasis formation. However, the precise contribution of tumour-induced systemic inflammation to metastasis and the mechanisms regulating systemic inflammation are poorly understood. Here we show that tumours maximize their chance of metastasizing by evoking a systemic inflammatory cascade in mouse models of spontaneous breast cancer metastasis.We mechanistically demonstrate that interleukin (IL)-1b elicits IL-17 expression from gamma delta (cd) T cells, resulting in systemic, granulocyte colony-stimulating factor (G-CSF)-dependent expansion and polarization of neutrophils in mice bearing mammary tumours. Tumour-induced neutrophils acquire the ability to suppress cytotoxic T lymphocytes carrying the CD8 antigen, which limit the establishment of metastases. Neutralization of IL-17 or G-CSF and absence of cd T cells prevents neutrophil accumulation and downregulates the T-cell-suppressive phenotype of neutrophils. Moreover, the absence of cd T cells or neutrophils profoundly reduces pulmonary and lymph node metastases without influencing primary tumour progression.Our data indicate that targeting this novel cancer-cell-initiated domino effect within the immune system-the cd T cell/IL-17/neutrophil axis-represents a new strategy to inhibit metastatic disease.